2012 - European Year for Active Ageing and Solidarity between Generations / 2012 - Evropsko leto aktivnega staranja in solidarnosti med generacijami - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
It has been 10 years since the General Assembly of the United Nations passed the International Plan of Action on Ageing. At the tenth anniversary of this event, the European Union announced that 2012 would be the European Year of Active Ageing and Solidarity between Generations.